2017
DOI: 10.1101/193706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Hoxd Cluster Is a Dynamic and Resilient Tad Boundary Controlling the Segregation of Antagonistic Regulatory Landscapes

Abstract: The mammalian HoxD cluster lies between two topologically associating domains (TADs) matching distinct, enhancer-rich regulatory landscapes. During limb development, the telomeric TAD controls the early transcription of Hoxd gene in forearm cells, whereas the centromeric TAD subsequently regulates more posteriorHoxd genes in digit cells. Therefore, the TAD boundary prevents the terminal Hoxd13 gene to respond to forearm enhancers, thereby allowing proper limb patterning. To assess the nature and function of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 92 publications
(142 reference statements)
9
88
0
Order By: Relevance
“…We found that deleting any individual CTCF site minimally altered predictions. Our model thus predicts this boundary is formed by redundant CTCF sites, a phenomenon observed experimentally in other genomic locations 3,4 .…”
supporting
confidence: 58%
“…We found that deleting any individual CTCF site minimally altered predictions. Our model thus predicts this boundary is formed by redundant CTCF sites, a phenomenon observed experimentally in other genomic locations 3,4 .…”
supporting
confidence: 58%
“…Nevertheless, this property of structural variants can be beneficial for characterizing the chromatin landscape if disruptions of multiple elements, e.g. bound CTCF sites, are required to alter the boundary activity of TADs, as appears to be the case at the HoxD locus (Rodríguez-Carballo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…TADs have therefore been proposed to act as functional regulatory units that favour contacts between enhancers and their target gene within a TAD whilst limiting aberrant interactions of enhancers across TAD boundaries (Fudenberg et al, 2016;Sun et al, 2019). In support of this, some studies have found that deletion or inversion of CTCF sites at TAD boundaries, can promote TAD boundary crosstalk and re-wire enhancer-promoter contacts (de Wit et al, 2015;Guo et al, 2015;Narendra et al, 2015;Rodríguez-Carballo et al, 2017). Moreover, a number of recent studies have suggested that changes to TAD structure can disrupt gene regulation through enhancer-rewiring in human disease (Flavahan et al, 2016;Franke et al, 2016;Lupiáñez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%